Leveraging Indigenous Knowledge Systems for Community-Based Education and Sustainable Development in Nigeria: Policy Insights from Edo State - Airhuoyo, Faith (Zenodo, 2025)
Across the world, the recognition of Indigenous Knowledge Systems (IKS) as foundational to sustainable development and participatory governance is gaining momentum. In Nigeria, IKS has long shaped rural education, social organization, environmental stewardship, and communal resilience, yet remains marginalized in formal policy frameworks. This paper examines how integrating IKS into public policy and governance can strengthen community-based education and inclusive development. Drawing from Elinor Ostrom’s (1990) theory of polycentric governance, which emphasizes multiple, overlapping centers of authority working collaboratively to address local challenges, and Paulo Freire’s (1970) concept of dialogical learning, alongside Fafunwa’s (1974) historical analysis of Nigerian education, Aina’s (2010) examination of higher education governance in Africa, and UNESCO’s (2018) framework on Education for Sustainable Development, the article situates IKS as a critical framework for participatory governance and context-sensitive policy design, drawing on key frameworks and insights from foundational and contemporary scholarship. Through a review of Nigerian experiences and comparative perspectives, it argues for policy models that honor local epistemologies, empower communities, and foster development outcomes grounded in indigenous worldviews. The paper concludes by calling for a paradigm shift from externally imposed interventions toward collaborative, knowledge-driven policies. These policies should integrate both indigenous and scientific perspectives in decision-making for sustainable and inclusive development.
This article examines how Indigenous Knowledge Systems (IKS) can strengthen community-based education and sustainable development in Nigeria, focusing on Edo State. Drawing on polycentric governance and participatory education frameworks, it argues for integrating local knowledge into policy and practice to promote inclusive, culturally grounded development.
Keywords: Indigenous Knowledge Systems; Community-Based Education; Sustainable Development; Inclusive Development; Education Policy; Participatory Goverance; Development Studies; Education; Edo State